Frozen Semen Quality of Simmental Cattle in Various Commercial Diluents - Komariah; M. L. Zuhdi; M. A. Tahar; T. Maulana (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2023)
This study determines the effect of different commercial diluents on the quality of frozen Simmental semen. The extraction of fresh semen from 3 Simmental bulls using an artificial vaginal method was performed twice a week. Fresh semen with motility of >70% was further processed to frozen using a one-step dilution method, and the commercial diluents used were Andromed®, Optixcell®, and Steridyl®. The diluted semen was packed into mini-straws, equilibrated, frozen, and stored for further testing. Data were analyzed by analysis of variance (ANOVA), followed by Duncan Multiple Range Test (DMRT) analysis with a 5% confidence level. The results showed that commercial diluents significantly affected motility, viability, intact plasma membrane, abnormalities, and recovery rate of frozen semen (P<0.05). Commercial diluents with different sources of lecithin reported different results on the quality of frozen semen. Steridyl® has a more optimal ability to maintain the quality of frozen semen of Simmental cattle, followed by Optixcell® and Andromed®.